Executive Committee Minutes 2017-04-13 - Academic Senate:::::::::
Agenda – Approved. Chair Report. President Report. Revision to the Cheating and Plagiarism policy approved for Senate agenda. Revision to the Student Grievance policy referred back to SAC. Provost Report. Certificate in Public History and Museum Studies approved for the Senate consent calendar. Statewide Senator Report. Change to UPRS charge referred to S&F. Revision to the Program Review policy approved for the Senate agenda. Revision to the RTP policy approved for the Senate agenda. Resolution – Faculty on Senate Diversity Subcommittee to serve on the President's Diversity Council approved for Senate agenda. Discussion of APARC priority recommendations put on Senate agenda. Revision to the Range Elevation for Lecturers policy approved for the Senate agenda. Vice Chair Report. Vice President of Administration and Finance Report. Vice President of Student Affairs Report. Senate Agenda approved. Associated Students Report. CFA Report.